2020
DOI: 10.1073/pnas.1918602117
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically scrambled nanocrystals are catalytically active for CO 2 -to-multicarbons

Abstract: Promotion of C–C bonds is one of the key fundamental questions in the field of CO2 electroreduction. Much progress has occurred in developing bulk-derived Cu-based electrodes for CO2-to-multicarbons (CO2-to-C2+), especially in the widely studied class of high-surface-area “oxide-derived” copper. However, fundamental understanding into the structural characteristics responsible for efficient C–C formation is restricted by the intrinsic activity of these catalysts often being comparable to polycrystalline copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 43 publications
2
152
0
Order By: Relevance
“…To follow the evolution in chemical state and morphology of electrocatalysts under stationary electrode potential conditions, operando X-ray-based 33 as well as in situ vibrational spectroscopies 31 , 34 36 , and in situ electrochemical transmission electron microscopy (TEM) 37 39 were used to record changes in catalyst chemical state 40 , 41 , local structure 13 , or intermediates 42 . However, to date, real-time tracking individual CO2RR product yields and product onset potentials on OD-Cu catalysts at fast time scales under non-stationary, transient conditions has remained very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…To follow the evolution in chemical state and morphology of electrocatalysts under stationary electrode potential conditions, operando X-ray-based 33 as well as in situ vibrational spectroscopies 31 , 34 36 , and in situ electrochemical transmission electron microscopy (TEM) 37 39 were used to record changes in catalyst chemical state 40 , 41 , local structure 13 , or intermediates 42 . However, to date, real-time tracking individual CO2RR product yields and product onset potentials on OD-Cu catalysts at fast time scales under non-stationary, transient conditions has remained very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu-based catalysts are the most promising electrocatalysts for converting CO 2 into C2 + products. [16][17][18][19] However, the most Cu-based catalysts generally favor the production of ethylene during CO 2 RR. [20][21][22][23] To improve the selectivity of C2 + alcohols, different methods have been applied to modify the Cu-based catalysts, including modifying morphology, [24] using two metals, [25] doping with a heteroatom, [26] and modifying with other molecules.…”
mentioning
confidence: 99%
“…In multi-carbon CO 2 RR, a large range of mechanistic hypotheses have also been indicated sometimes based on theoretical modeling [ 37 , 72 , 73 , 74 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. The proposals are different in terms of the mechanism, type of intermediates and active sites.…”
Section: Other Proposed Molecular Mechanisms Of Reactionmentioning
confidence: 99%
“…Other authors instead indicate the need to have specific surface sites on the electrocatalyst. Li et al [ 94 ] indicated that CO 2 to C2+ conversion requires an enriched disorder in the copper compared to crystalline Cu, obtained by electrochemical nanocrystal scrambling, i.e., the dynamic fusion of Cu nanoparticles under CO 2 reducing conditions to form multi-carbon active scrambled nanocrystals. It is not well described which new type of active sites forms in this scrambling mechanism, or the influence on the mechanism, but it is hypothesized that this leads to a higher population of strongly bound *CO (the asterisk indicates a surface-bound species), due to disorder-induced microstrain that alleviates the undesired repulsive interactions of a high density of bound *CO [ 102 ], comparable to the creation of optimal geometries in enzymatic systems.…”
Section: Other Proposed Molecular Mechanisms Of Reactionmentioning
confidence: 99%